Stability analysis of fuzzy-model-based control systems : linear-matrix-inequality approach - Lam, Hak-Keung; Leung, Frank Hung-Fat (Studies in fuzziness and soft computing, 2011)
Summarizing the latest work in the field, this book offers readers a number of approaches to designing stable and efficient FMB control systems, and includes detailed analysis and derivation steps to enable novices to follow the materials effectively